Non-invasive markers to predict Esophageal varices in patients with cirrhosis of liver: A hospital-based cross-sectional study - Joshi, Sanjeev; Giri, Rajendra Mani; Rokaya, Manish (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Esophageal varices are a serious complication of liver cirrhosis and a major cause of morbidity and mortality. Routine endoscopic screening, though recommended, is invasive and costly. This study aimed to evaluate noninvasive clinical, biochemical, and ultrasonographic parameters to predict the presence of esophageal varices in cirrhotic patients.Methods: A hospital-based prospective cross-sectional study was conducted at the OPD of the Internal Medicine Department over two years (June 2019-May 2021). A total of 73 patients with liver cirrhosis, diagnosed on clinical, biochemical, and ultrasonographic criteria, were enrolled. All patients underwent detailed clinical evaluation, blood investigations, abdominal ultrasonography, and upper gastrointestinal endoscopy. Esophageal varices were graded using the Paquet classification. Statistical analysis included the Mann-Whitney test, chi-square test, ROC curve analysis, and multivariate logistic regression.Results: Out of 73 patients, 78.08% had esophageal varices; 84.93% were male. Spleen diameter (SD) and portal vein diameter (PVD) had the highest AUCs (0.912 and 0.929, respectively). APRI (AUC: 0.868) and FIB-4 (AUC: 0.859) were also significant predictors. On multivariate logistic regression, SD >10.9 cm (OR: 4.013; p=0.037), PVD >11.7 mm (OR: 2.379; p=0.025), and FIB-4 >1.5 (OR: 2.283; p=0.046) were independent predictors of esophageal varices.Conclusion: Non-invasive parameters, particularly spleen diameter, portal vein diameter, and FIB-4 score, reliably predict the presence of esophageal varices in cirrhotic patients, enabling targeted endoscopy, primary prophylaxis, and improved resource utilization.